PENEGAKAN HUKUM PIDANA TERHADAP PEMBAKARAN HUTAN - Wira Adi Kusuma; M. Fadly Daeng Yusuf; Olivia Anggie Johar (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2026)
Forest burning is an environmental crime that causes significant damage to ecosystems, public health, and the economy. Within the jurisdiction of the Rokan Hilir Regional Police, forest burning continues to occur despite being prohibited and subject to criminal sanctions under several Indonesian laws, including Law Number 32 of 2009 on Environmental Protection and Management as amended by Law Number 6 of 2023, Law Number 41 of 1999 on Forestry, and Law Number 1 of 2023 concerning the Criminal Code. This study aims to analyze the criminal law enforcement against forest burning offenders within the jurisdiction of the Rokan Hilir Regional Police, identify the factors hindering law enforcement, and formulate efforts to optimize criminal law enforcement against such environmental crimes This research employs a sociological legal research method with a descriptive-analytical approach. Data were collected through interviews with law enforcement officers at the Rokan Hilir Regional Police and literature studies of statutory regulations, legal literature, and other supporting documents. The collected data were analyzed qualitatively and presented descriptively. The results indicate that criminal law enforcement against forest burning in the jurisdiction of the Rokan Hilir Regional Police has been carried out through investigation, inquiry, arrest, detention, and prosecution processes. However, its implementation has not yet been fully effective due to several obstacles, including difficulties in proving the perpetrators' involvement, the vast area affected by forest fires, limited personnel and infrastructure, challenging geographical conditions, low public legal awareness, and economic factors encouraging land clearing by burning. Efforts to optimize law enforcement include strengthening integrated patrols, enhancing inter-agency coordination, utilizing hotspot monitoring technology, conducting legal awareness campaigns for local communities, and consistently imposing criminal sanctions on offenders in accordance with applicable laws and regulations.